Bridging the gap in water governance: lessons from global practices and the transition to integrated Water Resources Management (IWRM) - Khamzayeva, F.; Baikushikova, G. (Farabi Journal of Social Sciences, 2024)
This study examines global experiences and best practices in water resources management, emphasizing the transition from traditional control-focused frameworks to Integrated Water Resources Management (IWRM). The analysis underscores the necessity for comprehensive, adaptive strategies in response to climate change, socio-economic shifts, and urbanization. Highlighting the success of collaborative models such as the European Union Water Framework Directive, the research identifies critical differences between the approaches of post-Soviet states and EU nations, particularly in public participation, goal-setting, and implementation strategies. Case studies demonstrate the economic and environmental benefits of innovative methods like wastewater reuse and advanced water purification technologies. The findings advocate for enhanced cooperation among stakeholders, comprehensive policy integration, and the adoption of modern assessment tools to improve water quality and sustainability. This work aims to inform policymakers and practitioners on developing efficient and equitable water governance systems that address current and future challenges. Keywords: Integrated Water Resources Management (IWRM), sustainable development, adaptive strategies, water framework directive, climate change.